(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
A broad range of fungi are among abundant organisms occur in the soil such as nematodes and interaction with each other so parasitic and predaceous relationships developed among most larger group of soil fungi from Basidiomycetes and phycomycetes, they are known as nematophagous fungi or nematodedestroying fungi. This paper focus a review of researchers carried out by various researchers on the variation trap formation and mechanisms of capturing nematodes.